Preface - Garcia, Leovino Ma. (Archīum Ateneo, 2024)
In this insightful study, Roger Burggraeve the eminent specialist on Levinas shows why Vasily Grossman’s masterpiece, Life and Fate fascinated the French-Jewish philosopher Emmanuel Levinas during the last decade of his life. According to Burggraeve, Grossman’s account of Stalin’s totalitarian State resonated with Levinas’s philosophy of the face and socio-political responsibility. Burggraeve envisions as his task to show the inextricable link between ethics, politics and responsibility in society. He accomplishes this in three symphonic movements. In a first movement, he describes Levinas’s quest for an alternative foundation for society beyond being, the otherwise than being. In a second movement, starting with the other of the Other, the third party, he stresses Levinas’s insistence on the ethical necessity of justice and the State. This is where Grossman’s account of the dark side of the State becomes thought-provoking for Levinas. In a third and final movement, Burggraeve brings out how Levinas surpasses every social-political regime by means of the human rights of the vulnerable Other(s) and by means of the “small goodness” which lifts the socio-political system into the Infinite and into the religious realm.